A systematic review of tranexamic acid in hip fracture surgery. (20th September 2016) - Farrow, Luke S.; Smith, Toby O.; Ashcroft, George P.; Myint, Phyo K.
Abstract : Aim: To systematically examine and quantify the efficacy and safety of tranexamic acid in hip fracture surgery. Methods: A systematic literature search was conducted using Medline, EMBASE, AMED, CiNAHL, and the Cochrane Central Registry of Controlled Trials. Two assessors independently screened search outputs for potentially relevant articles which met the eligibility criteria. The primary outcome measure was requirement of post‐operative blood transfusion. Risk of bias assessment was performed using the Cochrane Collaboration's risk of bias tool for randomized controlled trials (RCTs) and the ROBINS‐I tool for observational studies. Meta‐analysis was performed to estimate risk ratio (RR), risk difference (RD) and mean difference (MD) values for dichotomous and continuous data outcomes, respectively. The interpretation of each outcome was made using the GRADE approach. Results: Of 102 studies identified, seven met the inclusion criteria including a total of 770 participants (TXA: 341; Control: 429). On meta‐analysis, intravenous TXA resulted in a 46% risk reduction in blood transfusion requirement compared to a placebo/control group (RR: 0.54; 95% CI: 0.35–0.85; I 2 : 78%; Inconsistency (χ 2 ) P = <0.0001; n = 750). There was also a significantly higher post‐operative haemoglobin for TXA versus placebo/control (MD: 0.81; 95% CI: 0.45–1.18; I 2 : 46%; Inconsistency (χ 2 ) P = 0.10; n = 638). There was no increased risk of thromboembolic events (RD: 0.01; 95% CI: −0.03, 0.05; I 2 : 68%; Inconsistency (χ 2 ) P = 0.007, n = 683). Conclusion: There is moderate quality evidence that TXA reduces blood transfusion in hip fracture surgery, with low quality evidence suggesting no increased risk of thrombotic events. These findings are consistent with TXA use in other orthopaedic procedures.